Sdělování pravdy pacientům s onkologickým onemocněním: co je to pravda? - Surbone, Antonella (The lancet oncology CZ, 2007)
Attitudes and practices of truth-telling to people with cancer have shifted substantially in the past few years. However, cultural and individual differences persist, and some difficulties common to all medical specialties are magnified in oncology. In this Personal View, I review and analyse data for attitudes and practices of truth-telling worldwide. I also assess ethical justifications, with special reference to interpersonal aspects of patients' autonomy and the dynamic nature of truth in the clinical context. Examples are provided to show how this ethical perspective can help oncologists to frame the discourse on truth-telling and to find solutions to the dilemmas of whether, when, and how to tell the truth to their patients in clinical practice. Finally, I identify future targets for research.
Keywords: Neoplasms; nádory; Physician-Patient Relations; Humans; Ethics, Medical; lidé; sdělení pravdy; vztahy mezi lékařem a pacientem; Truth Disclosure; lékařská etika